1997
DOI: 10.1021/ba-1997-0253.ch001
|View full text |Cite
|
Sign up to set email alerts
|

From Electron Transfer Reactions to the Effects of Backbonding

Abstract: The initial motivation for extending the chemistry of ruthenium ammines was to provide new reagents for research on electron transfer reactions. Quite early in pursuing the preparative chemistry, an unexpected capac -ity of Ru(II) for backbonding was uncovered, and the systematic investi -gation of its influence on physical and chemical properties became a goal in its own right. The new directions led to the discovery of a num -ber of novel reactions, which in some cases led to novel products. The research has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The data collected on the system described here strongly demonstrated that the π back-bonding effect, so well established by Taube's research group, , from the [Ru(CN) 5 ] 3- metal center , plays an important role in the stability of the RupySAu improving the assessment of the ET of cyt c . To extend such study to other π-donor systems, experiments with [Fe(CN) 5 ] 3- , [Ru(NH 3 ) 5 ] 2+ , and [Os(NH 3 ) 5 ] 3+ metal centers are currently under investigation at our laboratory.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The data collected on the system described here strongly demonstrated that the π back-bonding effect, so well established by Taube's research group, , from the [Ru(CN) 5 ] 3- metal center , plays an important role in the stability of the RupySAu improving the assessment of the ET of cyt c . To extend such study to other π-donor systems, experiments with [Fe(CN) 5 ] 3- , [Ru(NH 3 ) 5 ] 2+ , and [Os(NH 3 ) 5 ] 3+ metal centers are currently under investigation at our laboratory.…”
supporting
confidence: 67%
“…We undertook the [Ru(CN) 5 ] 3- metal center as a π-donor system coordinated to the pyS ligand to design the first inorganic complex applicable to the assessment of the inherent rate of the cyt c ET reaction. A key point is that the coordination of a π-donor transition metal center to a nitrogen on a pyridine ring of the pyS would affect its electronic density, enhancing the C−S bond strength with consequent stability gain of the adlayer.…”
mentioning
confidence: 99%